(3GdeMce aj Yde fbW GdeUGMas - (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdMGaX GHh YeQh GdMeO ddg HGQi GdfSHe gPG cJGH ai Yde fbW GdeUGMa hcjajI Ydi CdaGX GdJdGhI hePGgH GdbQGO s
(3BNQgG (B:s
(3bGd CHh YeQh agPg CUhd GdfbW YdiePGgH GdfMGI GdeJbOejf hGJHGYg Je cJGH GdeMce ai Yde fbW GdeUGMa s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW bdjd GdfbW hHYV ChQGbgG HNW eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
Keywords: (3GdJaSjQ hYdhe GdbQBfs